A multi-case study of university students' language-learning experience mediated by mobile technologies: a socio-cultural perspective. Issue 3 (19th May 2017) - Ma, Qing
ABSTRACT: Emerging mobile technologies can be considered a new form of social and cultural artefact that mediates people's language learning. This multi-case study investigates how mobile technologies mediate a group of Hong Kong university students' L2 learning, which serves as a lens with which to capture the personalised, unique, contextual and ubiquitous nature of mobile language learning. The results suggest that Hong Kong university students make use of varied e-resources and tools for learning their L2; they also tend to combine L2 learning with subject learning, communication, entertainment and personal interests, and reveal distinctive features and attributes that form their personalised learning approaches. Based on these, a new socio-cultural framework is constructed to capture the key components involved in mobile technologies-mediated L2 learning and to describe the dynamism and interaction among the components, involving L2 agency, personalisation, tools, knowledge, communications and entertainment. In addition, L2 agency plays an important role in determining how learners employ mobile technologies in mediating and personalising their language learning. Factors that influence personalised mobile language learning are also unveiled. Finally, a number of implications are derived from the research findings to inform further research or practice with regard to mobile language learning.